A Virus Without Papers: Understanding COVID-19 and the Impact on Immigrant Communities. (June 2021) - Kiester, Elizabeth; Vasquez-Merino, Jennifer
The COVID-19 pandemic has exposed the inequalities facing vulnerable populations: those living in economically precarious situations and lacking adequate health care. In addition, frontline workers deemed essential to meet our basic needs have faced enormous personal risk to keep earning their paychecks and the economy running. Immigrant communities face an intersection of all three vulnerabilities (e.g., economic precarity, health care barriers, essential workforce), making them one of the most vulnerable populations in the United States. We conducted 26 interviews via Zoom with immigrant service providers in Pennsylvania and New York, including lawyers, case workers, religious leaders, advocates, doctors, and educators in order to gain a better understanding of the impact of COVID-19 on immigrant communities. These interviews affirmed that immigrants are concentrated in essential industries, which increases their exposure to the virus. In addition, they lack access to social safety nets when trying to access health care or facing job/income loss. Last, COVID-19 did not adequately slow the detention and deportation machine in the United States, which led to increased transmission of the virus among not only detainees but also others in the detention system, surrounding communities, and the countries to which people were deported, countries that often lacked an adequate infrastructure for dealing with the pandemic. Based on our interviews, we have a series of specific policy recommendations to diminish the vulnerability of immigrants and create social safety nets that will include them and protect them when the market fails to do so. Immigrants of all types have made indispensable contributions to the US economy during the pandemic and before it. First, Congress and states should pass legislation to provide COVID-19 relief payments to all essential workers, regardless of their status, as compensation for putting their lives on the line to keep the economy running. Second, as a public health imperative, federal and state governments should expand coverage of Medicaid and Children's Health Insurance Programs (CHIP) to include immigrant essential workers and their children, regardless of their status. Third, DHS should not refer essential workers to removal proceedings, and immigration courts should terminate all removal proceedings for essential workers without criminal records. When it comes to issues of health care affordability and access, Congress must continue to revise the Affordable Healthcare Act to expand coverage for those who do not qualify for Medicaid but earn too little to afford insurance on their own. Finally, there must be a review and rigorous enforcement of workplace health and safety standards, particularly when it comes to farming, meatpacking, food production, and food service industries. Our final recommendations are specific to DHS and two of the primary agencies they oversee: Immigration and Customs Enforcement (ICE) and the Border Patrol. First, there needs to be a review of ICE policies and practices, leading to a shift in policy that keeps mixed-status families intact and minor children out of detention centers and that streamlines and expands the asylum process. Second, both Congress and the administration must create additional paths to legal status where none now exist, including for recipients of Deferred Action for Childhood Arrivals (DACA) and for children who have arrived since June 2007.